Madrasas in India Organisational Climate and Issues - Khatun, Aliya (JOURNAL OF INDIAN EDUCATION, 2017)
Educational system is the backbone of the development of any country. Changes have taken place in education system according to the need of the time. Madrasa education system has a very important place in Indian society from its beginning. This system has played a silent but important role in educating millions of Muslims of the country. Organisational climate plays a very crucial role in outcomes of any institution. In case of Madrasas, there is a dire need of reform in its organisational climate, because traditional types of organisational climate of Madrasas are hardly able to cater the need and demand of the time. The present study is an effort to know about the organisational climate and issues of Madrasas in India.